1999
DOI: 10.1148/radiology.210.3.r99fe54639
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis: Influence of Early Pain Relief on the Accuracy of Clinical and US Findings in the Decision to Operate—A Randomized Trial

Abstract: Morphine does not improve US-based diagnosis of appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 12 publications
1
48
0
8
Order By: Relevance
“…3,6,18,22 However, this study showed that the overall clinical impression was similar with or without pain control. The administration of analgesics did not appear to affect the patient's disposition.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…3,6,18,22 However, this study showed that the overall clinical impression was similar with or without pain control. The administration of analgesics did not appear to affect the patient's disposition.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, some recent surveys have revealed that surgeons remain reluctant to provide early analgesia without a definitive diagnosis. 18 Previous studies enrolled all patients with acute abdominal pain, which caused some debate about the recommended sample size of future studies. In one study, only 7% of patients with acute abdominal pain were ultimately diagnosed with a condition that, if missed, might result in increased mortality or morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as the action of papaveretum is similar with opioids, the study is worthy for showing no significant negative effects of opioids on diagnostic accuracy. In 1999, Vermeulen et al [8] considered morphine versus placebo in the ED patients who were suspected of acute appendicitis, and the diagnostic accuracy was found to be 89% in the morphine group and 91% in the placebo group. Although the selected patient population of the study impeded the generalization of the results, which the authors of the study determined was a limitation, the strong pain relief and both the patient and physician comfort and satisfaction with morphine streamlined the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesia in the setting of undifferentiated abdominal pain has long been an area for controversy; the idea is that "covering the physical findings" will worsen outcomes [8,214]. Fortunately, there are sufficient data refuting this idea-an idea based upon historical cautions formulated due to problems with large opioid doses in the preradiology era-that the question has been answered to a reasonable degree of certainty [179,[215][216][217][218][219][220][221][222][223][224][225][226]. A variety of opioids (including the atypical agent tramadol) have been assessed, as administered a variety of ways ranging from IV bolus [227] to nebulized opioid [228] to patient-controlled analgesia [179], but the bottom line is that existing evidence does not support a practice of having patients suffer to preserve the physical examination [8].…”
Section: Special Issues Withmentioning
confidence: 99%